Combined Abundance of All Vulnerable Marine Ecosystem Indicator Taxa Inadequate as Sole Determiner of Vulnerability, Antarctic Peninsula - Lockhart, Susanne J.; Hocevar, John (Frontiers in Marine Science, 2021)
In order to achieve conservation objectives and preserve the biodiversity of the Southern Ocean, a variety of ecosystems must be protected. This holds especially true for the benthic communities of this region that are characteristically mosaic in their spatial distributions. As such, disparate communities cannot be comprehensively assessed by a single blanket methodology. Herein, evidence appropriate to the diverse characteristics of the communities encountered during a submarine expedition demonstrates the particular vulnerability of four sites that exemplify VMEs as defined by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) and the UN’s Fisheries and Agriculture Organization (FAO). Three sites are identified as VMEs based on highly significant abundances of indicator taxa. A fourth is identified based on a high density of cold-water coral taxa, many of which were not observed in abundance at the sites that were triggered as vulnerable by a significantly high abundance of all indicator taxa. The VME at this latter site was richly diverse in coral taxa, many of which are considered particularly vulnerable to climate change, as well as critical for their potential for genuine blue carbon sequestration. As of November, 2018, all four sites are now registered with CCAMLR as VMEs and thus, are afforded protection from all bottom fishing activities. However, if consideration isn’t given to the composition and/or diversity of VME indicator taxa present, in addition to overall abundance/density, some of the most vulnerable communities are left at risk. A blanket threshold for all VME taxa adhered to in fisheries management of the Southern Ocean, and other high seas areas, is grossly insufficient. Without taking a more precautionary approach to identifying and protecting VMEs, CCAMLR will not be able to meet its conservation objectives and may even be putting Antarctic fisheries at risk.